The Role of Kiss1 Neurons As Integrators of Endocrine, Metabolic, and Environmental Factors in the Hypothalamic–Pituitary–Gonadal Axis - Yeo, Shel-Hwa; Colledge, William H. (Frontiers in Endocrinology, 2018)
Kisspeptin-GPR54 signalling in the hypothalamus is required for reproduction and fertility in mammals. Kiss1 neurons are key regulators of gonadotropin-releasing hormone (GnRH) release and modulation of the hypothalamic-pituitary-gonadal axis (HPG). Arcuate Kiss1 neurons project to GnRH nerve terminals in the median eminence, orchestrating the pulsatile secretion of luteinizing hormone (LH) through the intricate interaction between GnRH pulse frequency and the pituitary gonadotrophs. Arcuate Kiss1 neurons, also known as KNDy neurons in rodents and ruminants because of their co-expression of neurokinin B and dynorphin represent an ideal hub to receive afferent inputs from other brain regions in response to physiological and environmental changes, which can regulate the HPG axis. This review will focus on studies performed primarily in rodent and ruminant species to explore the potential afferent inputs to Kiss1 neurons with emphasis on those located in the arcuate region but also considering those located in the rostral periventricular region of the third ventricle (RP3V). Specifically, we will discuss how these inputs can be modulated by hormonal, metabolic and environmental factors to control gonadotropin secretion and fertility. We also summarize the methods and techniques that can be used to study functional inputs into Kiss1 neurons.